THE DEVELOPMENT OF AN INSTRUCTIONAL TRAINING CURRICULUM OF PROBLEM SOLVING SKILLS BY USING SITUATION-BASED LEARNING FOR ELEMENTARY SCHOOL TEACHERS - Lekvilai, Supawan; Suntornsawate, Plisa (Academic Journal Phranakhon Rajabhat University, 2022)
The objectives of this research were 1) to develop an instructional training curriculum of problem solving skills by using situation-based learning for elementary school teachers, 2) to study instructional problem solving skills by using situation-based learning for elementary school teachers, and 3) to study students’ problem solving skills that received instructions from teachers who have been trained in an instructional problem solving skills by using situation-based learning. The population consisted of 1,552 elementary school teachers at educational institutions in Bangkok that was in the service area of Phranakhon Rajabhat University in the academic year of 2020. The samples consisted of 40 teachers who participated in the instructional training curriculum, however 6 teachers were voluntarily participated in the project, and 160 students from classrooms whose teachers were the sample group. The research tools were an instructional training curriculum of problem solving skills by using situation-based learning, a curriculum appropriateness assessment form, a test, questionnaires of satisfaction with the training, an instructional problem solving skills assessment form, and the students’ problem solving skills assessment form that was assessed in a 4 item multiple choice form with the reliability of 0.86. The statistics used to analyze the data were mean and standard deviation. The results showed that: 1.The problem-solving skills training curriculum by using situation-based learning for elementary school teachers was appropriate at a high level. The Post training on teachers’ instructional knowledge and understanding of problem-solving skills by using situation- based learning was higher than before the training. The teachers’ satisfaction towards the instructional training curriculum of problem-solving skills by using situation-based learning was at the highest level. 2. The instructional problem-solving skills by using situation-based learning of elementary school teachers who participated in the project were assessed from the teachers’ problem-solving skills lesson plans and observations of the teachers’ self-assessed and supervisor assessment of teachers’ instructional behavior of problem-solving skills was in overall at a high level and were all consistent. 3. The problem-solving skills of the students studying with teachers who participated in the project was higher after the experiment.